Analisis Pelaku Kenakalan Remaja “Klitih” dalam Perspektif Teori Asosiasi Diferensial Sutherland - Ciek Julyati Hisyam; Alma Miftaqiyah; Aryo Anargya Hakim Putra; Chieka Aisyah Kinanti; Dela Novi Ardani; Nadya Petricia Lubis; Sylmi Adila (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
This study aims to analyze the forms of deviant behavior commonly practiced by teenagers, one of which is "klitih" from Sutherland's perspective in the "Differential Association" theory. The author used a qualitative method by analyzing relevant reading sources, publications, and so on for this discussion. From the results of the conducted study, it is known that Sutherland's theory has a strong connection in explaining how perpetrators of "klitih," predominantly teenagers in Yogyakarta, are able to engage in actions that endanger themselves and the lives of others based on the premises that have been put forward.